Analysis of Traffic Noise in Two Cross-Sections at the Road Crossing The City - Andrzej Bąkowski; Leszek Radziszewski (Communications - Scientific letters of the University of Zilina, 2021)
The paper presents an analysis of the noise recorded by the two road traffic noise-monitoring stations. The stations were located in Kielce, Poland, at the road No. 74: on the outskirts of the city and near the center. Based on the experimentally recorded data, an equivalent sound level and acoustic pressure were determined for three sub-intervals of the day: nights, days and evenings. The conducted analyses showed that the average annual values (depending only on the time sub-intervals) of the median do not differ significantly between stations. A similar conclusion can be drawn based on simulations of the median and the C90 percentile of the sound pressure . However, the maximum relative differences in the C99 percentile of the acoustic pressure between stations are around 13%. The maximum relative differences in median pressure between stations are around 15% (for the time sub-interval nights).